Training in the inspectorate of education: looking to the future - Joseba Ozkoidi Pérez; Andoni Albeniz Bratos (ADIDE Federación, 2014)
The diverse background of education inspectors in our ever-changing society outlines the necessity of a solid initial training followed by a continuing training programme adapted to new contexts. Only by these means can the tandem training-innovation become a reality. To our understanding, the following four methodologies are the most suitable for this purpose: 1. Virtual or face-to-face Professional Practice Communities: as organized human groups. 2. Promoting interconnectivity between formal and informal learning through the available information technology techniques. 3. Knowledge acquisition through technology forecasting and competitive intelligence. 4. Learning in alliance: Learning processes are considered to be precursors of potential alliances.